PERAN PERILAKU KONSUMEN SEBAGAI MEDIASI PADA HUBUNGAN KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN - Tampubolon, Herikson; Novitasari, Evi (JURNAL ILMIAH EDUNOMIKA, 2025)
The purpose research is to determine how the quality of service and product quality affect purchasing decisions with consumer behavior as an intervening variable. The research method used is a quantitative method based on the approach of analyzing numerical data/numbers. Hypothesis testing in this study used SPSS. Data analysis techniques using classical assumption tests and path analysis. The sampling technique used in this study is simple random sampling with the Slovin formula. Sample of 60 respondents from a population of 150 people. The results of the Direct Influence study are The influence of service quality variables on purchasing decisions through consumer behavior is not significant . The study found that the indirect influence of service quality on consumer behavior is significant, consumer behavior on purchasing decisions is also significant. It is concluded that consumer behavior successfully mediates the influence of service quality on purchasing decisions. While the direct influence of product quality on purchasing decisions through consumer behavior is not significant. The indirect influence of product quality on consumer behavior is significant, consumer behavior on purchasing decisions is also significant. It can be concluded that consumer behavior successfully mediates the influence of product quality on purchasing decisions